2007
DOI: 10.1007/s11116-007-9119-7
|View full text |Cite
|
Sign up to set email alerts
|

User satisfaction with paratransit in competition with motorization in indonesia: anticipation of future implications

Abstract: The rapid pace of motorization throughout the world has changed travel behavior, which in turn has influenced every aspect of transport operations. This impact has also increasingly challenged the future existence of such road-based urban public transport as paratransit due to its characteristics and problems, especially in developing countries. Since creating satisfied users can help retain paratransit’s existence, this research aims to explore user satisfaction with paratransit service in order to anticipate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(94 citation statements)
references
References 11 publications
0
85
0
9
Order By: Relevance
“…Customer satisfaction is a measurement on the value of the products or services based on customers' past experiences and an overall evaluation to their experiences [17]. From the perspective of market, there are an increasing number of medical cosmetology centers, salon cosmetology shops, and skincare brands launched into the market and demand is growing.…”
Section: The Importance Of Customer Satisfactionmentioning
confidence: 99%
“…Customer satisfaction is a measurement on the value of the products or services based on customers' past experiences and an overall evaluation to their experiences [17]. From the perspective of market, there are an increasing number of medical cosmetology centers, salon cosmetology shops, and skincare brands launched into the market and demand is growing.…”
Section: The Importance Of Customer Satisfactionmentioning
confidence: 99%
“…Thus, transportation researchers have recently developed various scales to measure passengers' service quality perception (Hu and Jen 2006;Joewono and Kubota 2007;Park et al 2006). For example, Hu and Jen (2006) adopted a multistage scale development procedure to develop a passengers' perceived service quality scale of bus service.…”
Section: Conceptual Background and Research Hypothesesmentioning
confidence: 99%
“…More specifically, each of the dimensions was calculated as the mean score of each item in each dimension (e.g., Jen and Hu 2003;Joewono and Kubota 2007;Lin et al 2008;Park et al 2006). Researchers indicated that measuring service quality in this way may not accurately reflect the concept of service quality (Dabholkar et al 1996).…”
Section: Conceptual Background and Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…These have been highlighted as an important attribute that contributes to service quality. In a study conducted by Joewono and Kubota (2007), tangible aspects such as comfortable seats and good security were among the pertinent aspects of service quality. Their respondents claimed to be dissatisfied with the cleanliness of the vehicles and the bus stops.…”
Section: Tangiblesmentioning
confidence: 99%